The creation of the self and language : primitive sensory relations of the child with the outside world - Rosenfeld, David, ....- (London : Karnac, 2012)
'This book, with its accompanying DVD has made it possible for us to witness what David Rosenfeld's treatment of Benjamin, a young boy with a diagnosis of autism, was actually like. We can see for ourselves what was done, what was said; we can follow the steps by which Benjamin moved from being a child without language, in a state of perpetual panic-stricken screaming and flailing about, to being a “real kid” with friendships, doing well at an ordinary school. Witnessing this transformation is a profoundly moving experience. So is hearing the testimony of Benjamin's parents, who had been told repeatedly that there was no future for their son. It was their wish that his therapy should be more widely known about, in the hope that professionals could learn from it so that other families' lives might be transformed as theirs had been through “Dr David's” intervention. Everyone concerned with children with autism is in their debt.' (From the Introduction by Maria Rhode, Emeritus Professor of Child Psychotherapy at the Tavistock and Portman NHS Foundation Trust)
The DVD: Now I Am A Real Kid : Treatment of Autism, which accompanies this book, is in Spanish with English subtitles.
Includes bibliographical references and index.
Keywords: Autistic children -- Care -- Case studies; Autistic children -- Language; Autistische kinderen